Answer:
mass of astronaut is M 67.362 kg
Step-by-step explanation:
Given details:
spring constant k = 606 N/m
Time T = 0.848 s
The time period is
![T = (2\pi)\sqrt{(m)/(k)}](https://img.qammunity.org/2020/formulas/physics/high-school/5ysuxyi2um4sq6bohfsu7g8d6pljmou1l9.png)
So the mass of the empty chair is
![m = [(T)/(2\pi)]^2 k](https://img.qammunity.org/2020/formulas/physics/high-school/qgisl9hh57c95ap550scv0ryvou3ri920c.png)
![= [(0.848)/(2\pi)]^2*606](https://img.qammunity.org/2020/formulas/physics/high-school/z3ms777fm8c4srsb739c1vwlq8635n7nb0.png)
= 11.038 kg
When astronaut is sitting in the chair then the time period is
![T' = (2\pi)\sqrt{(m')/(k)}](https://img.qammunity.org/2020/formulas/physics/high-school/9kn7u9lt901bzra62jhaaf2n8j79h8veyv.png)
![m' = [(T')/(2\pi)]^2k](https://img.qammunity.org/2020/formulas/physics/high-school/v9bj8xfxak1xkmz33ecdi4ktxpcgm23i4g.png)
![=[(2.26)/(2\pi)]^2*606](https://img.qammunity.org/2020/formulas/physics/high-school/gfihz6f5a1y6nquqyzy77nuvzo2exou9qa.png)
m' = 78.40 kg
mass of astronaut is M = m' - m
= (78.40 kg) - ( 11.038 kg)
= 67.362 kg